Progressive fibrosing interstitial lung disease: clinical uncertainties, consensus recommendations, and research priorities - George, Peter M.; Kreuter, Michael (The lancet. Respiratory medicine, 2020)
Within the spectrum of fibrosing interstitial lung diseases (ILDs) is a subset of patients who have inexorable progression of pulmonary fibrosis despite treatment, which is known as the progressive fibrotic phenotype. Although the concept of progressive fibrosing ILD has been applied largely to patients with idiopathic pulmonary fibrosis (IPF), there is now an increasing focus on irreversible progressive fibrosis in a proportion of patients with a range of underlying ILD diagnoses. Evidence has emerged to support a possible role for antifibrotic therapy in these patients. In this Position Paper, we discuss the importance of retaining diagnostic scrutiny within the multidisciplinary team and suggest a multidomain definition for progressive fibrosis. We consider the potential role of antifibrotic drugs as second-line therapy in the treatment algorithm for patients with progressive non-IPF ILD. We highlight risk factors that might predispose individuals to developing progressive fibrosis. Finally, we discuss key uncertainties and future directions for research and clinical practice.